POTENTIAL INFORMATION MEDIA FOR VILLAGE PETANG BASED ON VIDEO TO PROMOTE TOURISM VILLAGE - Jiwa Permana, Agus Aan; Yoga Sucipta, Gede (Journal of Education Technology, 2020)
This paper provides a template for preparing papers for electronic production of the Journal of Education Technology. A This study aims to create a storyboard, and implement a video entitled Media Information Potential Tourism Village District Petang Badung Regency. The method used in making the Potential Information Media for Tourism Village in the District of Petang in Badung Regency is Non Linear (Computer or Digital), where this method uses tools such as a computer as an editing tool so that the editing process becomes more maximal. Experiments conducted by the author whether the video has gone according to the storyboard, Video Media Information Potential Tourism Village District Petang Badung District lasts 8 minutes. Implementation of the Material Expert Test to see whether the data and content applied to the video are correct with existing data or not. 85% of the results obtained from the Expert Test Material means that the video is Very Good to use. Implementation is carried out in the Media Expert Test to see whether the video can be used or not. 72.25% results means the video is good to use. The benefit of the Potential Information Village for Tourism Village in Petang Sub-District, Badung Regency is that the community can know about Petang Sub-district and the tourism potential contained in the Petang District in Badung Regency.